2014
DOI: 10.3109/08977194.2014.904300
|View full text |Cite
|
Sign up to set email alerts
|

Influence of growth factors and cytokines on angiogenic function of endothelial progenitor cells: a review ofin vitrohuman studies

Abstract: Growth factors and cytokines released at sites of injury and inflammation play an important role in stimulating endothelial progenitor cell (EPC) migration to these sites. A comparative analysis of the literature shows under neutral in vitro conditions (pH 7.4), several growth factors and cytokines influenced favorably indices of EPC angiogenic function. They included SDF-1, VEGF, PlGF, FGF-2, NGF and IL-1β. Others, e.g. TNF-α, have an unfavorable influence. SDF-1 and VEGF in combination increased chemotactic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 72 publications
0
31
0
2
Order By: Relevance
“…Interestingly, although these cells are also pro‐angiogenic, their increased presence did not positively impact pro‐angiogenic genes. Instead, both VEGF and CXCL12, which are implicated in the recruitment, arrangement, and proliferation of endothelial cells, are downregulated …”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, although these cells are also pro‐angiogenic, their increased presence did not positively impact pro‐angiogenic genes. Instead, both VEGF and CXCL12, which are implicated in the recruitment, arrangement, and proliferation of endothelial cells, are downregulated …”
Section: Discussionmentioning
confidence: 99%
“…TNF-α is one of the critical pro-inflammatory cytokines. Peplow (22) reported that TNF-α has an unfavorable influence on cell migration and apoptosis. In order to further study the influence of IL-10 on EPCs, EPC functions were tested under the inflammatory microenvironment induced by TNF-α.…”
Section: Discussionmentioning
confidence: 99%
“…(11,12) Recruited endothelial progenitor cells (EPCs) from the bone marrow migrate to and differentiate into mature endothelial cells at the relevant sites of inflammation, where the cells are incorporated into blood vessel repair and neovascularization. (13) VEGF not only promotes angiogenesis by inducing proliferation, migration and capillary-like tube formation of EPCs (14,15) ; accumulating evidence reveals that VEGF is regulated by microRNAs (miRNAs) at multiple levels during angiogenesis. (16,17) These miRNAs are small, noncoding RNA molecules that control gene expression, map to introns of protein-coding genes, and function as key posttranscriptional regulators of gene expression and RNA silencing.…”
Section: Introductionmentioning
confidence: 99%